Shelf Life Determination of Pineapple Juice Using Extended Storage Studies (ESS) Method - Wardhani, Asri Puspita (Food Science and Technology Journal (Foodscitech), 2019)
Pineapple is one of perishable horticultural commodities that usually consumed in fresh form. Based on that, commercial food processing technology are required to extend shelf life of product. Shelf life product information is necessary before product launched in the market to ensure and guarantee the customers. The object of this research was to determine shelf life of pineapple juice that estimated by using ESS (Extended Storage Studies) method. Pineapple juice with preservative (0.05% sodium benzoate) and no preservative was processed, packaged and stored at chilling temperature (7°C) and room temperature (25°C). The juices were analyzed for the sensory attributes such as, taste, aroma, appearance, and viscosity. Sensory test was stopped when the panelist refused to do test for bubble, foam and mold growth on the surface, fermentation aroma appeared, and viscosity of pineapple juice increased. The shelf life were estimated to be 14 week for pineapple juice stored at 7°C with preservative (T1B1), 10 week for pineapple juice stored at 7°C without preservative (T1B2), 2 week for pineapple juice stored at 25°C with preservative (T2B1)and less than 2 week for pineapple juice stored at 25°C without preservative (T2B2). Therefore, chilling combined with use of preservatives are able to retard spoilage and slowed down deterioration of sensory attributes in pineapple juice.